2016
DOI: 10.1111/bij.12803
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history ofTrachylepisskinks in the Seychelles islands: introgressive hybridization, morphological evolution and geographic structure

Abstract: The Seychelles is a remarkably interesting archipelago for evolutionary studies, but only recently have molecular markers been used to explore its biogeographic patterns. Here we used morphological and molecular data to examine diversity and phylogenetic relationships of two endemic skink sister-species from this archipelago: Trachylepis sechellensis and Trachylepis wrightii. Mitochondrial DNA genealogy rendered a monophyletic T. wrightii nested within a paraphyletic T. sechellensis, whereas nuclear DNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
2
7
0
Order By: Relevance
“…The spatial structuring of phenotypic and genetic variation within H. rostratus (especially the partitioning into northern-and southern-island groups) is broadly similar to that observed within Seychelles lizards (38,(43)(44)(45)82,83), frogs (39,47) and crabs (46). This spatial (and temporal) pattern is likely caused by rising sea levels sundering formerly widespread populations and/or IBD across Association between the different datasets (Table 3) strongly supports the general patterns of genetic and morphological variation being explained by isolation-by-distance (IBD) rather than isolation-by-adaptation (IBA) within H. rostratus.…”
Section: Discussionsupporting
confidence: 59%
“…The spatial structuring of phenotypic and genetic variation within H. rostratus (especially the partitioning into northern-and southern-island groups) is broadly similar to that observed within Seychelles lizards (38,(43)(44)(45)82,83), frogs (39,47) and crabs (46). This spatial (and temporal) pattern is likely caused by rising sea levels sundering formerly widespread populations and/or IBD across Association between the different datasets (Table 3) strongly supports the general patterns of genetic and morphological variation being explained by isolation-by-distance (IBD) rather than isolation-by-adaptation (IBA) within H. rostratus.…”
Section: Discussionsupporting
confidence: 59%
“…1). This pattern of differentiation is documented in studies across a range of taxa, including the geckos Ailuronyx (Rocha et al, 2016a), Phelsuma (Rocha et al, 2013), Urocotyledon (Rocha et al, 2011); and the skinks Pamelaescincus (Valente et al, 2013) and Trachylepis (formerly Mabuya) (Rocha et al, 2016b). However, within this north-south biogeographic pattern, further evidence of cryptic diversity is beginning to emerge in several taxa (e.g.…”
Section: Introductionmentioning
confidence: 82%
“…Recently identified phylogeographic patterns within the archipelago's endemic herpetofauna have revealed a variety of geographic correlations: skinks and geckos broadly differentiate into northern (Praslin and surrounding islands) and southern (MahĂ©, Silhouette, and surrounding islands) groups (Rocha et al, 2010;Rocha et al, 2011;Valente et al, 2013;Rocha et al, 2016a;Rocha et al, 2016b); while for the nonsooglossid anurans, a distinct lack of variability is shown in the multi-distributed treefrog Tachycnemis seychellensis (Maddock et al, 2014), conflicting with observed structuring in Seychelles endemic caecilians (Adamson et al, 2016;Maddock et al, 2016;Maddock et al, 2017). Our mtDNA analyses appear to confirm the relationship posited by Taylor et al (2012), namely that Silhouette and Praslin populations of So.…”
Section: Biogeographic and Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BSP model assumes a single panmictic population and violation of this assumption can result in misleading demographic inferences [ 72 , 73 ]. Although BSP assumes a single species or monophyletic group in analyses of demographic history, similar analyses have been carried out when modelling hybridization at population peripheries [ 74 , 75 ]. Thus, we generated BSPs for genetically homogenous geographic populations as inferred by AMOVA (e.g., [ 34 , 74 , 75 ]).…”
Section: Methodsmentioning
confidence: 99%